Deconstructing The Risky Link And Match Policy: Training Of Trainers (TOT) On Human Trafficking Mitigation For High School and Vocational High School Guidance And Counseling Teachers - Rindu Erwin Marpaung; Valentina Moiso (PT. TAROMBO RESEARCH DEVELOPMENT, 2026)
This community service program aims to enhance the capacity of Guidance and Counseling (BK) teachers across SMA and SMK in Pematangsiantar City and Dairi Regency as early detection agents against such threats. The implementation utilized a Training of Trainers (ToT) approach, including conceptual presentations from public policy and political sociology perspectives, followed by Focus Group Discussions (FGD) with 60 participants. The results revealed a profound information asymmetry, where the evolution of digital TPPO remains a novel issue for educators. A crucial finding during the FGD indicated institutional vulnerability at the vocational school level (SMK) due to structural pressures from the Link and Match policy. Educational institutions are implicitly indicated to potentially facilitate human trafficking chains unintentionally (unintentional complications) due to the absence of due diligence mechanisms regarding the legality of employment agencies. This program concludes the necessity to deconstruct the illusion of instant social mobility in student career counseling